(3JMUjd Yjf GdPgH ef eYOf LhgQ GdCOH aj Yde eLGRGJ GdYQHs - (3CHhGdMLGL jhSa Hf SdjeGf Hf YjSi GdCfOdSj GdeYQha HGdCYde GdTefJQjs; (3YeQh Hf YKeGf Hf bfHQ GdMGQKj HGdhdGA, CHh HTQ, GdedbH SjHhjg,J (B180 (3g` s ((3EHQGgje Hf Ydj Hf MSjf GdQHYj s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG gPG cJGH CeQ HJCdjag hJdNjUg hJgPjHI GdeYJVO HGddg GdefUhQ s
(3BNQgG (B:s
(3hEf cGf CaVd efg cGdLjaI JWah Ydi GdeGA hJYdhg ced cJGH Ydi MSH eG CeQ Hg Gdedc GdLdjd GdeYJVO HGddg GdefUhQ s
(3GfXQ GdLRA GdChd (B31 (3fMhs
(3hKGfjI aj GdLRA GdChd (B110 (3COHs
(3hgPG GdcJGH TQM ThGgO cJGH SjHhjgs
(3GdfSNI ebGHdI s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdfMhs